A problem-based learning approach to develop metacognition and writing performance of Nigerian undergraduates - Aliyu, Muhammad Mukhtar (2017)
Writing is an essential language skill for undergraduates. However, many Nigerian undergraduates display various problems when writing in English. In order to develop writing skills, there is a need to develop metacognition as it influences writing.However, there is an absence of studies that explore learning approaches to be used in developing students’ metacognition. Therefore, the aim of this study is to investigate the effects of a problem-based learning (PBL) approach on metacognition and the writing performance of Nigerian undergraduates. The study employed a mixedmethod convergent parallel design. The participants involved in the study were an intact class of 18 second-year students taking English Composition course in a college in North-eastern Nigeria. The study was conducted over a period of 12 weeks. The quantitative data were collected through the participants’ writing activities, a metacognitive questionnaire which was administered before and after the PBL treatment, and a PBL questionnaire which was administered at the end of the whole PBL treatment. Paired-sample t-test analysis was run to compare the mean scores of the pre- and post-treatment writing scores and metacognitive scores. The results showed that there were significant improvements in the content, organisation,vocabulary, language use and mechanics of the participants’ post-treatment writing scores. The statistical analysis of the metacognitive questionnaire revealed significant improvements in the participants’ metacognition. Specifically, the results showed that the PBL approach had significant effect on the participants’ awareness of metacognitive knowledge of task requirements, personal learning process, strategy use, text and accuracy, problem-solving and discourse features. The results of the PBL questionnaire showed the participants’ positive perceptions of the use of the PBL approach in a writing classroom. The qualitative data were collected from the participants’ interactions during the PBL process and through semi-structured interviews and reflective journal writing. The analysis of the qualitative data revealed that tutor facilitations and peer collaboration involved in the PBL process helped and encouraged the participants to employ metacognitive strategies effectively to generate viable solutions to ill-structured problems and collaboratively developed their writing. The study suggests PBL as an alternative method to be used in writing classrooms, especially in the Nigerian context. The study also offers theoretical and pedagogical implications and recommendations for further research.